Membangun Potensi Kemandirian Ekonomi Santri Pada Pondok Pesantren Mambaul Ulum Mojokerto - Aditya Surya Nanda; Fitryani Fitryani (Seminar Nasional Teknologi dan Multidisiplin Ilmu (SEMNASTEKMU), 2023)
Mamba'ul Ulum Mojosari Islamic boarding school is one of the Islamic boarding schools that has economic independence. This Islamic boarding school has several superior products which have extraordinary potential if marketed appropriately. Apart from that, the concept of entrepreneurship in the era of digital transformation 4.0 is also very important as initial capital towards successful entrepreneurship today. The target to be achieved is how the school (in the Islamic boarding school environment) connects and internalizes the teachings of entrepreneurship and the contribution of economic development to the Islamic boarding school environment, through making products made by Mamba'ul Ulum Islamic boarding school students which will then be sold on e-commerce . This research uses a qualitative-descriptive method, the research results illustrate how the principles created as the basis for the entrepreneurial spirit of santri are useful for improving the economy in the Islamic boarding school environment with the aim of developing economic independence among the santri environment, increasing knowledge and understanding of entrepreneurial potential. There are results achieved in making products to be marketed. The use of online marketing media is simple, mentoring is provided by subject teachers to maintain stable abilities and understanding